(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2018)
The ampulla of Vater encompasses the openings of both the common bile duct (CBD) and pancreatic duct (PD). Presently ERCP has allowed better observation of the papillae in ectopic locations. The diagnosis of ectopic papillae can be done by radiological studies also but they are expensive and not affordable by all patients so most of the cases of ectopic papillae are identified by ERCP. An ectopic location, distal to the second part, in the third or fourth parts of duodenum has been described frequently but a proximal location is rare. Only a few cases have been found to be located in the gastric, pyloric and duodenal bulb areas. We report three such rare cases of anomalous ectopic ampullae discovered during the performance of ERCP from the Department of Gastroenterology, Combined Military Hospital, Dhaka and also a short review of the literature. In these three subjects one papilla was located in the pylorus and other two in the first part of the duodenum. All of them presented with features of choledocholithiasis with cholangitis. They were successfully managed by therapeutic ERCP. Clinical implications of these rare anomalies and anatomical variations can assist the gastroenterologists in effective patient management. J Bangladesh Coll Phys Surg 2018; 36(1): 37-40